Metastatic Biphasic Primitive Tumor in the Mandible of a Child - Pinheiro, Tiago Novaes; Leite, Milena Gomes Melo; Bindá, Fábio Arruda; Dutra, André Luiz Tannus; Sarmento, Naelka; Cabral, Lioney Nobre; Consolaro, Alberto; Bacchi, Carlos Eduardo (European Journal of Dentistry, 2020)
Pediatric mandibular tumors present an aggressive biological behavior and difficult diagnosis. A wide range of odontogenic and nonodontogenic tumors comprise the spectrum of these lesions. We report a case of a 1-year-old male child patient showing facial asymmetry symptomatic of an expansive lesion extending throughout the body and ramus of the left hemimandible with a diameter of 8 cm. The histopathological report suggested a high-grade mucoepidermoid carcinoma (MEC), recommending further immunohistochemical investigation of the ectomesenchymal or neuroectodermal origin of the tumor cells. The patient evolved with extensive bilateral pleural effusion followed by metastasis in the middle third of the right humerus, and died 2 months after the first biopsy procedure by acute renal failure with tubular necrosis, before a final inconclusive immunohistochemical report was reached. The lack of resources for less-favored regions of Brazil impairs rapid biomolecular examinations such as immunohistochemical resulting in delay of appropriate therapeutic procedures.
Keywords: PNET; mucoepidermoid carcinoma; carcinosarcoma; Ewing’s sarcoma; odontogenic tumors; metastasis